PENGARUH TERAPI PSIKORELIGI TERHADAP PENURUNAN PERILAKU KEKERASAN PADA PASIEN SKIZOFERNIADI RUANG RAWAT INAP RUMAH SAKIT JIWA DAERAHPROVINSI LAMPUNG TAHUN 2018 - Sari Narulita; Mella Yuria; Isti Istianah (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2019)
Background: The period of pregnancy and postpartum is the period when hormonal imbalance and adjustment become a mother (social factor) that makes a woman transition both physically and psychologically. Physically, the phases of pregnancy and postpartum greatly contribute to the increasing rate of obesity in women.Purpose: This study aims to analyze the relationship between body mass index and postpartum women's anxiety level in Sukabumi City in 2014.Methods: This research type is survey research using Cross Sectional method. The target population of the study was women who underwent labor in Sukabumi city of West Java with a sample of 97 people using random sampling technique.Results: From the analysis of the relationship between body mass index and postpartum anxiety level there was a significant relationship. From the results of analysis of body mass index relationship with mild anxiety level and moderate-severe anxiety there is no significant relationship.Discussion: The need to provide counseling about preparing before pregnancy or before birth in women. So that women are ready physically and mentally in pregnancy and labor so that it can reduce the number of anxiety disorders in postpartum women.